The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1471-0528.15982
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive versus routine episiotomy among Southeast Asian term pregnancies: a multicentre randomised controlled trial

Abstract: Objective To determine whether restrictive or routine episiotomy in term pregnant Southeast Asian women results in fewer complications.Design A multicentre randomised controlled trial.Setting Two tertiary and two general hospitals in Thailand.Population 3006 singleton pregnant women 18 years or older, ≥37 weeks of gestation, cephalic presentation and planned vaginal delivery.Methods This randomised controlled trial compared routine versus restrictive episiotomies in Thai women giving birth vaginally. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…The rates of episiotomy are still very high in Asian nations, such as 86% in Vietnam, 27 60% in India 14 and 94.5% in Cambodia. 12 China had been considered to have a high rate of episiotomy for a long time. When referring to high rates of episiotomy, China is often cited as an example, with an episiotomy rate of around 80%.…”
Section: Discussion a Gap In Rates Of Episiotomy Still Exists Between Asia And Europementioning
confidence: 99%
See 2 more Smart Citations
“…The rates of episiotomy are still very high in Asian nations, such as 86% in Vietnam, 27 60% in India 14 and 94.5% in Cambodia. 12 China had been considered to have a high rate of episiotomy for a long time. When referring to high rates of episiotomy, China is often cited as an example, with an episiotomy rate of around 80%.…”
Section: Discussion a Gap In Rates Of Episiotomy Still Exists Between Asia And Europementioning
confidence: 99%
“…9 Another study also suggested that episiotomy is used only if there was an indistinct indication of imminent tearing. 7 There is wide variation in the rates of episiotomy all over the world, from developed countries such as Denmark (4%), 10 Sweden (9.7%), the UK (12%-15%) and the USA (11.6%) 11 12 to developing countries including Saudi Arabia (45%), 13 India (60%), 14 Jordan (67%), Yemen (75.1%), 15 Cambodia (94.5%) 16 and China Taiwan (100%), 12 which are still very high compared with the 10% recommended by the WHO. 6 However, in 2010, the prevalence of third-degree or fourth-degree tears was not significantly different in Denmark (4.1%), Sweden (3.5%), the UK (2.4%-3.2%), the USA (4.9%), India (2.1%) and China (4.9%).…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Barnfield et al for using our paper for the discussion in their journal club and raising a few questions about the methodology for clarification.…”
mentioning
confidence: 99%
“…We read with interest the article ‘Restrictive versus routine episiotomy among Southeast Asian term pregnancies: a multicentre randomised controlled trial’ which generated good discussion in our Journal Club. We congratulate the authors Sangkomkamhang et al for writing a paper on this very pertinent topic.…”
mentioning
confidence: 99%